PROBLEMATICS CULTURE OF CHILD MARRIAGE IN INDRAMAYU IN A LEGAL AND CULTURAL PRESFECTIVE - Hazar Kusmayanti; Dede Mulyanto (UNISSULA, 2020)
The problem of marriage is a very common problem for the world community, especially the people of Indonesia, one of the problems is child marriage. the highest likelihood of child marriage is in Indramayu Regency. The purpose of this study is to analyze the practice of child marriage that occurs in Indramayu, the reasons for child marriage. The method of the approach taken by the author is to use a normative juridical approach. Based on the research findings there are obstacles that cause child marriage culture in Indramayu as follows: There are religious views that allow underage marriages, There are differences in legal perspectives between traditional and contemporary fiqh, aspects of tradition and culture in the local area Modern communication technologies such as mobile phones encourage young marriages. The implication of this research is to socialize Law Number 16 the Year 2019 regarding marriages regarding the marriage age limit up to 18 years for men and women as well as government cooperation with community leaders, religious leaders and the Indonesian Women's Coalition to eradicate child marriage in various regions.